THE ISSUE OF MANAGING THE INTERNATIONALIZATION OF THE UNIVERSITY (ҚазҰУ хабаршысы. Экономика сериясы, 2019)
The scale of internationalization of higher education in the CIS countries, along with theimpact of this process on the socio-economic and cultural development of the regions, once againdemonstrates the need for its close study, analysis of the experience of other countries, evaluation of theresults of previous research in this area. Thus, this paper attempts to characterize the main trends in thedevelopment of research on the internationalization of higher education by comparing the competenciesof the CIS countries with the EU countries and some Asian countries. The article also discusses thephenomenon of multidimensional integration processes in higher education, analyzes the main facts thataffect the process of internationalization.The aim of the study is a theoretical and methodological analysis of the constructive experience ofinternationalization of the educational process in EU and CIS universities.Research methods: structural analysis and synthesis development of foreign researchers allowed toisolate in the complex phenomenon of internationalization of universities the basic elements that havea decisive influence on the nature of the object of study; methods of comparative analysis, that allowedto establish the similarities and differences between the processes of internationalization of universitiesin advanced foreign countries and Kazakhstan, as well as an integrated approach, allowing to considerthe phenomenon of internationalization of universities in its relationships and dependencies with otherprocesses and phenomena in the context of globalization.The results of the study can be defined within the conduct of case studies of internationalizationof European universities and the findings of prominent researchers, and, on this basis, to identify theneed of implementation of internationalization processes actually contributing to the development ofthe modern University, improving its competitiveness on the internal and external market of educationalservices and research.